2017
DOI: 10.1093/humrep/dew341
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial DNA content of cumulus granulosa cells is linked to embryo quality

Abstract: This work was supported by the University Hospital of Angers, the University of Angers, France, and the French national research centres INSERM and the CNRS. There were no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 35 publications
4
48
2
Order By: Relevance
“…Recent studies have proposed quantifying mtDNA in cumulus, granulosa and trophectoderm cells to predict embryo quality and viability (Desquiret-Dumas et al, 2017;Diez-Juan et al, 2015;Fragouli et al, 2015;Ogino et al, 2016). Boucret et al (2015) concluded that the mtDNA content in cumulus cells is correlated with the amount detected within the oocyte for each cumulus-oocyte complex.…”
Section: Biogenesis Of Mtdna and Copy Numbermentioning
confidence: 99%
“…Recent studies have proposed quantifying mtDNA in cumulus, granulosa and trophectoderm cells to predict embryo quality and viability (Desquiret-Dumas et al, 2017;Diez-Juan et al, 2015;Fragouli et al, 2015;Ogino et al, 2016). Boucret et al (2015) concluded that the mtDNA content in cumulus cells is correlated with the amount detected within the oocyte for each cumulus-oocyte complex.…”
Section: Biogenesis Of Mtdna and Copy Numbermentioning
confidence: 99%
“…To the authors’ knowledge, this study is the first to report that FF impacts mitochondrial biogenesis in cumulus cells, but molecular events underlying the increase in biogenesis is a subject for further experiments. Nevertheless, studies have shown that the mtDNA copy number in cumulus cells reflects a high yield of good embryos in humans . Thus, a beneficial effect of FF on oocyte developmental competence is associated with an increased mtDNA in cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have shown that the mtDNA copy number in cumulus cells reflects a high yield of good embryos in humans. 26,27 Thus, a beneficial effect of FF on oocyte developmental competence is associated with an increased mtDNA in cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy embryos, the accumulated mtDNA is divided equally among all cells during embryogenesis . Recent studies have proposed quantification of mtDNA in cumulus, granulosa, and trophectoderm cells as a promising strategy for predicting embryo quality and viability . Since mtDNA content in cumulus cells is correlated with that in oocytes for each cumulus‐oocyte complex, it is suggested that the mitochondrial characteristics of the cells may serve as a marker of the oocyte quality .…”
Section: Factors Influencing Oocyte Qualitymentioning
confidence: 99%
“…[61][62][63][64] Recent studies have proposed quantification of mtDNA in cumulus, granulosa, and trophectoderm cells as a promising strategy for predicting embryo quality and viability. 62,65 Since mtDNA content in cumulus cells is correlated with that in oocytes for each cumulus-oocyte complex, it is suggested that the mitochondrial characteristics of the cells may serve as a marker of the oocyte quality. 40 Furthermore, mutations or deletions in mtDNA have been correlated with organelle dysfunction, low ATP levels, and embryonic developmental arrest.…”
Section: Mitochondriamentioning
confidence: 99%